Implemantasi Paradigma Integratif dalam Empat Keterampilan Berbahasa Indonesia pada Kurikulum 2013 di Madrasah Ibtidaiyah - Fifi aris Wulandari; Muqowim Muqowim (Islamadina : Jurnal Pemikiran Islam, 2022)
The 2013 curriculum is a character-based curriculum with a themed learning system called thematic learning. Thematic learning refers to the integration of one subject with another through the use of subjects that can provide students with meaningful experiences. In learning, general subjects are often combined, while Islamic religious subjects exist independently, because Islamic religious subjects and general subjects are not combined in the teacher and student theme books. And subjects in Indonesia. Indonesian language has four skills that are closely related to Islam and student life. This article uses a library research method that uses literacy journals, books, and data related to the topic. From the literature research, it was found that Indonesian language skills include four skills, namely listening skills, reading skills, speaking skills, and writing skills. From an Islamic perspective, these four skills are closely related to student life. As is the case in Q.s Al Alaq chapters 1-5 and in the 2013 curriculum, the skills to read novels entitled Negeri Lima Menara contain prominent values, namely religious values, honesty, and discipline. Listening skills are contained in Qs Muhammad verse 21 and Qs Al A'raf verse 157 and in teaching and learning activities the teacher tells the story of the National Hero, so the character values that students can take from the story are religious values, honesty, hard work, trust, and never give up that can be applied by students in their daily life. Speaking skills are stated in Q.s Toha (20): 25-28 and the teacher gives the task of telling a story in front of the class about the story of the National Hero so that students can form character values that believe in themselves, discipline, courage, creativity and innovation. Writing skills as stated in Q.s. An-Nahl (125) and the teacher gave the task of making rhymes that would provide imaginative character values, intelligence, and creativity which were expected to form good character for students in society, nation and state.